2016
DOI: 10.1149/2.1091608jes
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Supported Nanocrystalline Manganese Oxide: Surpassing Platinum as Oxygen Reduction Catalyst in Direct Borohydride Fuel Cells

Abstract: Manganese oxide (MnO 2 ) nanodispersed on high surface area carbon was tested as cathode catalyst for direct borohydride fuel cells with an anion conducting membrane. In order to investigate the effects of borohydride crossover, ex-situ experiments toward oxygen reduction reaction were conducted employing rotating disk electrodes in presence of borohydride and thiourea. Although platinum showed superior catalytic properties at ideal conditions, manganese oxide outperformed platinum significantly in presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The EOR activities and stabilities of carbon supported Pd-based electrocatalysts were determined by means of cyclic voltammetry (CV) and chronoamperometry (CA) using a rotating disk electrode (RDE; Model AFE5T050GC from PINE Research Instrumentation), respectively [37,[40][41][42].…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…The EOR activities and stabilities of carbon supported Pd-based electrocatalysts were determined by means of cyclic voltammetry (CV) and chronoamperometry (CA) using a rotating disk electrode (RDE; Model AFE5T050GC from PINE Research Instrumentation), respectively [37,[40][41][42].…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…A MnO 2 /C catalyst was also prepared and tested as a cathode catalyst for DBFCs using an anion exchange membrane (AEM). 9 DBFC using MnO 2 /C exhibited a higher open-circuit voltage (0.88 V) than that using Pt/C (0.84 V). Chronoamperometry tests showed that the DBFC using MnO 2 /C (57.4 mA cm −2 ) presented a higher current density than that using Pt/C (28.9 mA cm −2 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in fuel cells, carbon paper acts as a conducting catalyst support and as a hydrophobic gas diffusion layer allowing reactant gas (hydrogen or oxygen) to access the catalyst. 10 Many studies have been performed to modify the surface properties of carbon paper and other carbonaceous materials to enhance electrochemical performance or to increase the operating lifetime. These include, but are not limited to, surface activation, modification of the pore size distribution, and functionalization with surface functional groups by employing suitable pretreatment methods.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These properties enable, in some cases, the use of carbon paper for several functions in the same electrochemical device. For example, in fuel cells, carbon paper acts as a conducting catalyst support and as a hydrophobic gas diffusion layer allowing reactant gas (hydrogen or oxygen) to access the catalyst …”
Section: Introductionmentioning
confidence: 99%